Ecology-Based Outdoor Activity As an Early Childhood Learning Strategy In the Aftermath of the COVID-19 Pandemic - Ammy Ramdhania; Heny Djoehaeni (SEAMEO CECCEP, 2022)
The impact of the COVID-19 pandemic on the world of education has been extraordinary. Learning at school is not running optimally. As a result, there is a decrease in the ability of knowledge and skills (learning loss) in students. Early childhood loses the opportunity to stimulate all the senses in their learning environment. In the period after the COVID-19 pandemic, early childhood needs activities that are able to increase their ability to build knowledge and skills from their learning experience. This study was conducted to analyze the ecology-based outdoor activity learning strategy in PAUD in the period after the COVID-19 pandemic. It is hoped that cognitive, motor, language and social-emotional development can be further honed and there will be improvements. This research was conducted at an early childhood education institution in the city of Cimahi. Using descriptive qualitative research methods, based on the constructivism paradigm, the researchers collected data through interviews and observations of relevant sources. Data analysis was obtained by induction to facilitate researchers in compiling more accurate research results. The triangulation technique was carried out to check the validity of the data by comparing the results of interviews and observations. Through FGD researchers get final conclusions that are relevant to the conditions in the field. The results of this study show that most of the cognitive, motor, language and socio-emotional development of early childhood after the pandemic experienced significant development through ecological-based outdoor activity learning strategies. The results of this study can be used as reference material in determining various learning strategies adapted to the situation and conditions of each institution.